Leer la ciudad: de lo urbano a lo poético - autor, Sin (Revista de Filología Románica, 2009)
By means of a diachronic analyses of the studies regarding the functions of urban space in literature a methodological approach is presented. Directed to channel the studies of the city towards a direct relation with literature and arts, in the theoretical text Topographies of the city, by Eugenia Popeanga Chelaru. A series of literary samples are presented, organized in relation to specific elements. Without pretending thoroughness, the church, the house, the market, the hotel and the graveyard are considered as fundamental spaces of the urban landscape and its imaginary representation. Some of the functions of this elements are studied, specially in the construction of the text by means of diverse rhetoric articulators, from the frame to the metaphor, as well as are studied the diverse literary subversions of the rhetoric models received, looking forwards to a subsequent amplification in a monograph on the literary representations of the city.